Use of Saponins as an Effective Surface Modifier in Cellulose Nanocomposites - Cherian, Bibin Mathew [UNESP]; Leão, Alcides Lopes [UNESP]; Caldeira, Mariana da Silva [UNESP]; Chiarelli, Daniele [UNESP]; de Souza, Sivoney Ferreira [UNESP]; Narine, Suresh; de Morais Chaves, Marcia Rodrigues [UNESP] (Taylor & Francis Ltd, 2012)
The present paper deals with the extraction of saponins from the pericarp of Sapindus mukorossi to use as compatibilizer in nanocomposites. The nanofibrils extracted from banana fibres are utilized as reinforcement of nanocomposite. These nanofibers were treated with Saponin, GPS (3-Glycidoxypropyltrimethoxysilane) and APS (3-Aminopropyltriethoxysilane) to compare the effectiveness of surface treatment. The effectiveness of surface modification was reflected on the increase in mechanical (tensile test, flexural modulus, impact test) properties and decrease in the RMS (Roughness Measurement System) roughness investigation by SFM (Scanning force microscopy) analysis.
Keywords: Banana nanofibres; nanocellulose; nanocomposites; saponins; surface modification